Rachunek kosztów działań – odpowiedź na zwiększone potrzeby polskich uczelni wyższych w zakresie informacji kosztowej - Klaus, Agata (Activity Based Costing – the answer on accrued requirements of polish universities in range of cost information, 2008)
Universities are units with expanded organizational structure, they accomplish compound services (instructive, scientific) and have differentiated recipients of their activities (students of each department, external enterprises, etc.). Therefore, management of these institutions of higher education is very complicated. The article presents the factors and suggests use of proper techniques of providing managerial information by educational institutions. The technique is Activity Based Costing.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 152-161